Smart drier / Muhamad Saufuan Hussin, Muhammad Izdihar Samsuri and Muhamad Aisamuddin Mohd Anuar - Hussin, Muhamad Saufuan; Samsuri, Muhammad Izdihar; Mohd Anuar, Muhamad Aisamuddin (2013)
The main function of the smart drier is to dry the clothes with supplying heat to the drawer within specific duration. Besides that, the duration of heating is set by timer. Heat release according to the temperature set, the circuit operates on a +5V single supply, keep the temperature at 75 Celsius degree, the heater circuit uses LM335 temperature sensor from National Semiconductor. To convert AC to DC transformer is used, transistor 78L12 is used for output 12V. The process of drying clothes is also supported by rotating the motor in the hangar system. It is not only for drying the clothes, but it can also be applied to any fabric such as shoes, blanket, mattress and etc.